Suitability of online 3D visualization technique in oil palm plantation management - Che Mat, Ruzinoor; Nordin, Norani; Zulkifli, Abdul Nasir; Mohd Yusof, Shahrul Azmi (2016)
Oil palm industry has been the backbone for the growth of Malaysia economy.The exports of this commodity increasing almost every year.Therefore, there are many studies focusing on how to help this industry increased its productivity.In order to increase the productivity, the management of oil palm plantation need to be improved and strengthen.One of the solution in helping the oil palm manager is by implementing online 3D visualization technique for oil palm plantation using game engine technology.The potential of this application is that it can helps in fertilizer and irrigation management.For this reason, the aim of this paper is to investigate the issues in managing oil palm plantation from the view of oil palm manager by interview. The results from this interview will helps in identifying the suitable issues could be highlight in implementing online 3D visualization technique for oil palm plantation management.